The Effectiveness of using Animated Short Video on Students’ Writing Ability in Narrative Text - Ragil Sedya Pangestuti; Patuan Raja; Desy Awal Mar'an (U-Jet Unila Journal of English Language Teaching, 2026)
This study examined whether animated short videos could improve students’ narrative writing ability. The research used a quantitative one-group pre-test and post-test design with one class of twelfth-grade students. Narrative writing tests were given before and after three teaching sessions using animated short videos. The results showed that students’ narrative writing ability increased after the treatment. Animated short videos helped students develop ideas, organize paragraphs, and understand narrative structures more clearly. Improvements were found in several aspects of writing, including content, organization, grammar, mechanics, style and quality of expression. Statistical analysis showed a significant difference between the pre-test and post-test scores, indicating that animated short videos had a positive effect on students’ writing ability. Therefore, animated short videos can be considered an effective medium for teaching narrative writing in senior high schools.